Finding Your Way Around the HILDA Survey Data - Watson, Nicole (My University, 2021)
The Household, Income and Labour Dynamics in Australia (HILDA) Survey data is a valuable resource for researchers and policy makers. The HILDA Survey is a nationally representative household panel study with 20 waves of data collected between 2001 and 2020. This article helps researchers new to the HILDA Survey gain an understanding of the survey, the data and its documentation.
The Australian Economic Review
Keywords: Surveys and survey methodology